The application of hydrogen and photovoltaic for reactive power optimization. (27th March 2020) - Lin, Rongheng; Ye, Zezhou; Wu, Budan
Abstract: Hydrogen and photovoltaic (PV) are two typical new energies, which are important to sustainable development. Introducing hydrogen or PV into smart grid as distributed generation (DG) becomes a promising approach. These kinds of power generations will help the grid gather more energy and introduce new chances of grid management. In this paper, we will introduce an application of hydrogen and PV in reactive power control. PV is used for hydrogen harvest, and PV is variable and dependent on weather conditions compared with a conventional generator that produces a stable output. Photovoltaic hydrogen fuel cell (PV- H 2 -FC) is introduced as DG, which connects to the grid. Adding hydrogen-based DG would help improve the quality of supply power. A genetic algorithm for DG site selection supporting DG cost optimization is proposed. Reactive power optimization (RPO) is an important function in planning for the future and daily operations of the smart grid system. Implementation of reactive power optimization based on the historical solution matching is also proposed, it considers the PV- H 2 -FC features and grid historical data, which uses Cosine distance for similarity measurement. The proposed RPO algorithm has a great advantage in calculation speed compared with traditional algorithms. The historical load data with the highest similarity are extracted, and its historical RPO scheme is applied to simulate the current RPO scheme. Results show that this method could help to find out an RPO solution effectively. The proposed solution would provide processing purposes for power company information data and further explore the supporting role of information resources in grid operations, which has broad social benefits.